Literatura em foco: a formação intelectual de Vivaldi Moreira em O menino da mata e seu cão Piloto - Samantha Guedes Barbosa (2023)
This study investigated the intellectual formation of Minas Gerais writer Vivaldi Wenceslau Moreira from his literary readings in the autobiographical-memorialistic work O menino da mata e seu cão Piloto. The characterization of the autobiography and memoir genres was discerned; the different reading mediators were identified and a theoretical discussion about the role of this intellectual through his ideas and actions was done. It was possible to get to know more about a multifaceted profile of a writer that accomplished a variety of intellectual activities, read and wrote excessively, obtained with the authorities its own headquarters for the Academia Mineira de Letras and later on an important help to construct the attached Auditorium that gained his name. At late 20‟s and early 30‟s especially, with Era Vargas, where there is the centralization of power, the discussion of the role of intellectuality in Brazil rises, bringing the debate about the relation between political action and intellectual thought. The polarization between the isolated intellectual and that integrated to the political context is refuted, as we verify the coexistence between ideas and politics in the life of Vivaldi Moreira, and much more than stiffness definition, we validate the authenticity and responsibility of his choices, his appreciation for books, as well as much of his work still open to be explored.